Analysis of income level and welfare of fishing gear fishers in Barombong Village, Makassar City South Sulawesi Province - Roswiyanti Roswiyanti; Andi Ummung; Andi Nur Apung Massiseng (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
This study aimed to analyze the income level of fishing gear fishers and analyze the welfare level of fishing gear fishers in Barombong Village, Makassar City, South Sulawesi Province. Techniques data collection is done using observation, interviews using questionnaires and documentation. The type of data collected is data that is by the prosperous family indicators based on the 2019 BPS, namely; income data, household consumption or expenditure data, living conditions, household facilities, the health of family members, ease of obtaining health services, ease of entering children into education level and ease of securing transportation facilities. This research was carried out in Barombong Kacan Tamalate Village, Makassar City, in February - April 2021. The results showed that fishing gear fishermen respondents' average income per year was Rp. 36,905,833/year or Rp. 3,075,486/month and fall into the category of low-income level. Based on the 2019 BPS indicators, it is known that 24 respondents from 10 groups of fishing gear fishermen in the Barombong Village, Makassar City belong to the high welfare level as many as  8 respondents (33%) with a total indicator score of 20. As many as 16 respondents (67%) belong to the moderate welfare level with total indicator scores ranging from 18-19. Based on these results, it can be seen that the standard of living of fishing gear fishers in the Barombong Village, Makassar City, is classified as prosperous, with the fact that the income of respondents is low. Still, most of the life support has been provided by the government, especially in the health and education sectors, so that it does not burden household expenses. The addition of new jobs needs to be done as another source of income to increase welfare from a moderate level of interest to a high level of welfare.